Profil Kematangan Karir Siswa Kelas XI SMA Negeri 15 Medan dan Implikasinya Terhadap Layanan Bimbingan dan Konseling - Linda Lestari Hasibuan; Mirza Irawan (INDONESIAN COUNSELING AND PSYCHOLOGY, 2020)
This research aims to : (1) find out the description of career advancement of students in school in general and in terms of gender variables (male and female) and majors (IPA and IPS) (2) aswell as formulating Guidance and Counseling programs related to maturity Student careers in class XI 15 Medan 15 High School in Academic Year 2017/2018. The approach used in this research is a quantitative approach with descriptive methods. The sample in this study was 68 students of class XI SMA Negeri 15 Medan with sampling taken by simple random sampling lottery method. Data collection techniques used in this study were to spread the questionnaire and then analyzed using descriptive analysis and statistical analysis methods. Furthermore, the results of this study indicate that: (1) career maturity of class XI students of SMA Negeri 15 Medan in terms of gender variables (male and female) indicating that men were in the very high category of 6 people (29%), 11 people (52%) were in the high category and 4 people (19%) were in the medium category, while the female gender variable was in the very high category as many as 20 people (43%), 26 people (55%) including in the high category and 1 person (2%) included in the medium category. the career maturity of grade XI students of SMA Negeri 15 Medan in terms of the majors variable shows that students majoring in Natural Sciences are in the very high category of 14 people (44%), 16 people (50%) are included in the high category, and 2 people (6 %) included in the medium category, while social studies majors were in the very high category as many as 12 people (33%), 21 people (58%) included in the high category, and 3 people (9%) were included in the medium category based on the data above, (2) formulated Guidance and Counseling programs that contain annual programs, semester programs, monthly programs and weekly programs related to the career development field with the sub-field development of student career maturity in schools.